Knockdown THOC2 suppresses the proliferation and invasion of melanoma - Zhou, Xiaowei (Bioengineered, 2019)
Melanoma is a potentially fatal form of skin cancer with great metastatic potential. THOC2 plays a vital role in human biological progression, however, the roles of THOC2 in melanoma tumorigenesis are still unknown. In the present study, our data demonstrated that THOC2 expression was significantly increased in melanoma tissues, and high THOC2 expression was associated with poor overall survival of melanoma patients. THOC2 reduction repressed melanoma cell proliferation and invasion, and induced cell apoptosis in vitro. Microarray data revealed that the cAMP signaling pathway was significantly downregulated in A375 cells transfected with si-THOC2, which was further confirmed by RT-qPCR and bioinformatics analysis. In conclusion, our data indicated that THOC2 might act as an oncogene in melanoma progression through cAMP signaling pathway regulation, which may offer a therapeutic target for melanoma treatment.